2003
DOI: 10.1080/09593330309385626
|View full text |Cite
|
Sign up to set email alerts
|

A new technology for the treatment of mercury contaminated water and soils

Abstract: A new technology has been developed for the treatment of contaminated water and soils with lignin derivatives. It has been demonstrated that this technology can be used in the process of removal of high levels of mercury from water, and in the immobilization of leachable mercury in contaminated soils. Lignin derivatives contain an abundance of oxygen-containing functional groups such as phenolic, carboxyl, sulfonyl, alcoholic and enolic structures, which will form lignin-metal macromolecular complexes with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Lignin seems likely to interact with a variety of metal ions (Claye et al 1996; Guillon et al 2001; Merdy et al 2002; Wang et al 2005; Mohan et al 2006). Zhuang et al (2003) developed a technology for the treatment of Hg‐contaminated water and soils by using lignin derivatives contain phenolic, carboxyl, sulfonyl, alcoholic and enolic structures, and confirmed that the lignin derivatives are capable of combining with other metal ions such as Cr, Cu, Pb, Zn, Ni and Al. Moreover, polyphenols can interact with metals such as Cu, Zn and Fe via chelation through their aromatic hydroxyl groups (Seidel et al 2000; Hider et al 2001; Mira et al 2002).…”
Section: Resultsmentioning
confidence: 88%
“…Lignin seems likely to interact with a variety of metal ions (Claye et al 1996; Guillon et al 2001; Merdy et al 2002; Wang et al 2005; Mohan et al 2006). Zhuang et al (2003) developed a technology for the treatment of Hg‐contaminated water and soils by using lignin derivatives contain phenolic, carboxyl, sulfonyl, alcoholic and enolic structures, and confirmed that the lignin derivatives are capable of combining with other metal ions such as Cr, Cu, Pb, Zn, Ni and Al. Moreover, polyphenols can interact with metals such as Cu, Zn and Fe via chelation through their aromatic hydroxyl groups (Seidel et al 2000; Hider et al 2001; Mira et al 2002).…”
Section: Resultsmentioning
confidence: 88%
“…The mercury adsorption properties of FLD have been studied and discussed in the author's previous publication [12,16]. However, this is still a new challenge for FLD to stabilize the leachable mercury in BPS with high salt contents.…”
Section: Sequence Of Bps/pc/fld Treatmentmentioning
confidence: 99%
“…In a S/S process, the Hg-contaminated solid wastes [5,6] are mechanically mixed with a stabilizing agent, such as trisodium salt of trimercapto-s-triazine (TMT) [7], sulfur [8], fly ash [9], Portland cement (PC) [10], lignin derivatives [11,12], polymers [13] or other wastes [14][15][16][17]. Thus, Hg-contaminants may be immobilized through a chemical bonding [12,16] by the additive, or be enclosed with S/S additive or binder. The solubility and changes of mercury binding forms in contaminated soils have been studied at different pH values [18] after immobilization with alkali-polysulfide and TMT.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have shown that lignin derivatives are efficient adsorbents for the removal of toxic metal traces such as chromium (Lalvami et al, 2000;Dupont and Guillon, 2003), copper (Sciban and Klasnja, 2004;Wieber et al, 1988), lead (Crist et al, 2004;Lalvani et al, 1997a;Srivastava et al, 1994), zinc (Wieber et al, 1988;Lalvani et al, 1997b), nickel (Basso et al, 2002a), cadmium (Basso et al, 2002b), and mercury (Zhuang et al, 2003;Ray et al, 2002), as well as for pesticides (Rupp and Zuman, 1992), surfactants and dyes (Perineau and Gaset, 1981), phenols, polycyclic aromatic hydrocarbons and chlorinated hydrocarbons (Dizhbite et al, 1999;O'Neil et al, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Lignin derivatives obtained as sub-products of the paper pulp industry, such as lignosulfonates (sulfonated products) or alkaline lignin, also contain oxygen-bearing functional groups including phenols and carboxylics as well as sulfonylic groups. Thus, the polyanionic characters of these derivatives together with their polymeric flexibility allow their successful use as adsorbents in various systems (Zhuang et al, 2003).…”
Section: Introductionmentioning
confidence: 99%